Implementasi Program Layanan Call Center Manado Siaga 112 Studi Di Dinas Komunikasi Dan Informatika Kota Manado - Muyu, Yulven Leonardo; Londa, Very Y.; Lotulung, Levianne (Sam Ratulangi University, 2023)
This study aims to analyze the implementation of the Manado standby 112 call center service program in Manado City. The research was conducted from March to April 2023 in the Regional Technical Implementation Unit (UPTD) room located on the 2nd floor of the Manado City Hall building. The data analysis technique used in this study is an interactive qualitative technique. The results of the study are that there are several things that can support emergency complaint services maximally. The first factor is good cooperation between OPDs, where all OPDs join in carrying out the emergency complaint service process in this program. Friendly, fast and responsive service is the second factor, because this program does require fast service in dealing with emergencies in the City of Manado.